2019
DOI: 10.1042/bsr20192466
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling as a useful therapeutic target in hepatoblastoma

Abstract: Hepatoblastoma is a malignant tumor in the liver of children that generally occurs at the age of 2–3 years. There have been ample evidence from the preclinical as well as clinical studies suggesting the activation of Wnt/β-catenin signaling in hepatoblastoma, which is mainly attributed to the somatic mutations in the exon 3 of β-catenin gene. There is increased translocation of β-catenin protein from the cell surface to cytoplasm and nucleus and intracellular accumulation is directly linked to the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 79 publications
0
36
0
Order By: Relevance
“…Profiling expression of β-Catenin protein (β-Cat), its downstream target glutamine synthetase (GS), and its interactor Glypican-3 (GPC3) could be helpful in the identification of altered Wnt/β-Cat pathways. Thus, immunohistochemical co-expression of β-Cat, GS, and GPC3 observed in HCC suggests that GPC3-induced activation of the Wnt/β-Cat pathway is responsible for the development of malignant hepatocellular tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Profiling expression of β-Catenin protein (β-Cat), its downstream target glutamine synthetase (GS), and its interactor Glypican-3 (GPC3) could be helpful in the identification of altered Wnt/β-Cat pathways. Thus, immunohistochemical co-expression of β-Cat, GS, and GPC3 observed in HCC suggests that GPC3-induced activation of the Wnt/β-Cat pathway is responsible for the development of malignant hepatocellular tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yes-associated protein (YAP)1 has been reported to be related to tumor development and it cooperates with other signaling pathways. It has been reported that Wnt/βcatenin works in association with Hippo/YAP to induce the development of hepatoblastoma 33,34 . We suspect that miR-125b-5p targets and regulates YES1, causing changes in related signaling pathways that are involved in the progression of HB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several research groups have proposed the therapeutic effects of HB by specific inhibition of Wnt/β-catenin pathway, through a number of post-transcriptional measures such as short interfering miRNA, RNAs (siRNA), and bioactive small molecules. Hence, the Wnt/β-catenin signaling pathway is a valuable target for the development of therapeutic measures of HB ( Koch et al, 1999 ; Takayasu et al, 2001 ; Koch et al, 2005 ; Cairo et al, 2008 ; Eichenmüller et al, 2014 ; Sumazin et al, 2017 ; Sha et al, 2019 ). However, HB has the lowest mutation burden among all known cancer types, and the genetic determinants of HB remain to be further investigated ( Gröbner et al, 2018 ).…”
Section: Liver Diseases Uniquely Present In Children and Their Splicing Regulationmentioning
confidence: 99%
“…However, several genes, including IGF2, fibronectin, DLK1, TGFb1, MALAT1, and MIG6, were overexpressed in HB versus HCC. HB is genetically characterized by abnormal activation of the Wnt/β-catenin signaling pathway (Sha et al, 2019). Generally, extensive evidence has suggested that mutations in the β-catenin gene exon 3 are responsible for the activation of the Wnt/β-catenin signal transduction pathway in HB.…”
Section: Splicing Mutation In Hepatoblastomamentioning
confidence: 99%